A role of art is in socialization of personality - Maksymov М. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article is sanctified to consideration of problem of socialization of personality facilities of art. It is shown that modern sociocultural environment, in particular the phenomena of mass culture, not always positively influences on forming of personality. The necessity of address is well-proven to the standards of classic art with the purpose of harmonious development of personality.